2013
DOI: 10.1016/j.urology.2012.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Benign Prostate Glandular Tissue at Radical Prostatectomy Surgical Margins

Abstract: Objective To determine whether presence of benign glandular tissue at the radical prostatectomy surgical margin is associated with technique (open (ORP) or robotic assisted laparoscopic radical prostatectomy (RALRP)) and if benign glandular tissue increases the risk of biochemical recurrence. Methods Surgical specimens from men with clinical T1–T2 disease who underwent RP between 2004–2010 were re-reviewed by a single uropathologist, examining all sections from the prostate apex and base for the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…However, patients with CapI had a lower BCR compared to patients with EPE and PSM. Other studies focused on the impact of CapI into benign tissue only and failed to show a significant association with bRFS (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…However, patients with CapI had a lower BCR compared to patients with EPE and PSM. Other studies focused on the impact of CapI into benign tissue only and failed to show a significant association with bRFS (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Some groups reported that the rate of surgical margins with benign prostatic tissue was as high as 60% after RP. 25,26 Many patients receive salvage therapy, mainly ADT, in response to biochemical failure after RP or radiation therapy without posttreatment imaging. 27 In the current study positive findings on posttreatment imaging were associated with salvage treatment, suggesting that posttreatment imaging may influence subsequent management.…”
Section: Discussionmentioning
confidence: 99%
“…Odisho et al have reviewed 274 patients with benign glandular tissue at the surgical margin after radical prostatectomy. They concluded that this finding was not associated with postoperative elevation of PSA [ 15 ]. Thus, it seems that the only significant source of PSA after radical prostatectomy may be retained malignant cells and PSA kinetics early after the surgery are key to identification of patients with prostate cancer who have received failed prior therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently introduced ultrasensitive PSA detection techniques are offering a new insight into the changes in serum PSA at very low concentration. It has been demonstrated that after a properly performed radical prostatectomy, measurable PSA is most likely attributed to the presence of active prostate cancer cells rather than to retained benign prostatic tissue [ 15 , 16 ]. It is therefore conceivable, that real candidates for immediate adjuvant therapy, who have active prostate cancer cells remaining in the body after the surgery, should present with higher postoperative serum PSA in a comparison to individuals with incorrect diagnosis of PSM.…”
Section: Introductionmentioning
confidence: 99%